2021
DOI: 10.21608/ejabf.2021.137091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bioaccumulation and biosedimentation of some heavy metals on some biochemical responses in the sole fish, Solea solea inhabiting Lake Qarun, Egypt.

Abstract: Impact of bioaccumulation and biosedimentation of some heavy metals on some biochemical responses in the sole fish, Solea solea inhabiting Lake Qarun, Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Results concur with that of Mohamed (2019) and Elwasify et al (2021) who found that Cu, Fe and Zn concentrations increased in fish liver. Remarkably, the higher accumulation in liver may be due to its detoxification function and may influence its physiological responses and histological structure (Ferguson, 1989;Ghanem, 2019;Elwasify et al, 2021).…”
Section: Concentration Of Heavy Metals In An Aquaticmentioning
confidence: 99%
See 2 more Smart Citations
“…Results concur with that of Mohamed (2019) and Elwasify et al (2021) who found that Cu, Fe and Zn concentrations increased in fish liver. Remarkably, the higher accumulation in liver may be due to its detoxification function and may influence its physiological responses and histological structure (Ferguson, 1989;Ghanem, 2019;Elwasify et al, 2021).…”
Section: Concentration Of Heavy Metals In An Aquaticmentioning
confidence: 99%
“…The drainage water discharged into the lake is highly concentrated with solids, nutrients, pesticides, heavy metals and organic matters. It resembles about 450 million cubic meters of agricultural drainage water and domestic waste water that decreases annually to attain balance by evaporation (Mohamed, 2009;Ghanem, 2011;Mohamed, 2019;Elwasify et al, 2021). Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings were compared to contemporary climate change forecasts in order to assess their impact on future recruitment levels. Elwasify et al (2021) found that the biochemical composition of S. solea varied from season to season. S. solea is an important fish species.…”
Section: Introductionmentioning
confidence: 98%
“…These metals are toxic to human and aquatic organisms [Rubalingeswari et al, 2021]. The high accumulation of heavy metals in fish inhibits the growth rate by hampering the activity of metabolic enzymes [Elwasify et al, 2021]. According to Edogbo et al, [2020], the consumption of fish contaminated by Cd has the potential to pose a risk to human health [Edogbo et al, 2020].…”
Section: Introductionmentioning
confidence: 99%